State-owned Enterprise Performance Measurement Based on the 2016 Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) - Restianingati, Vindha Tyas (Universitas Muhammadiyah Sidoarjo, 2023)
PT. XYZ is a state-owned enterprise that contributes to national sugar production. In running its business, the company requires performance measurement to see how far the company has achieved. This study provides an overview of performance measurement with the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) approach. This study uses a literature review and descriptive analysis. The results of the assessment show that the score achieved by PT. XYZ in 2016 was 415.75 points and was included in the early improvement performance class. Although the results have not been maximized, several assessment categories have important aspects that support the company's performance. The category that dominates and gets the highest rating is the overall Product and Process Results category with 44 points. Meanwhile, the category that has a low rating is Operations Focus for the Operational Effectiveness indicator with a score of 16 points. In the future, PT. XYZ needs to restructure its work system, supply chain management, and improve monitoring and evaluation.